BIOLOGI REPRODUKSI IKAN NIPI (Hemiramphus far) DI PERAIRAN LAUT PANTAI UTARA KABUPATEN TIMOR TENGAH UTARA - Ludgardis Ledheng; Theresia Adelina Maria Mau; Blasius Atini (Politeknik Pertanian Negeri Kupang, 2018)
Nipi fish (Hemiramphus far) was the important resources of foods for peoples in TTU regency. The knowledge about data and information of reproductive biology of nipi fish was unknown and very limited. The objective of this research was to know reproductive biology of nipi fish and its implementation, and than it can be used as the source of learning, the first or primary data, and the important of information in study of fishing biology in resources the management sustainable. The research was conducted in Biology Laboratory of Timor University and it analyzed using statistic quantitative and descriptive covered length and weight distribution, sexual ratio, gonad maturity level, gonad somatic index, and fecundity. The samples of nipi fish was taken by random sampling at lampara or drawing trawl in the oceanic waters of north beach of TTU regency. The result of this research showed that during 5 months from December 2015 until April 2016 the total samples were 144 fishes comprised 90 females and 54 males dominated by female fishes. The highest distributionof the length for male and female was 27-28 cm. The weight of female was 58-65 gr, male fishes was 50-57 gr. The sexual ratio between male and female was not balance or not significantly (not 1 : 1) with the ratio was 1 : 1,66 or 37,5 % : 62,5 %. TKG dominated by TKG III and IV in March – April that indicated have been entered the season of climax spawner. The IKG of female fishes was heigher than the male with percentage above 19% was 19,99% ready to spawning. The everage of the fecundity was 300 eggs.